Usher Based on a Story by Edgar Allan Poe - Poe, Edgar Allan (Flicker Alley, 2013)
Harrington’s final film before he died in 2007, "Usher" is a remake of a short he made in high school based on the classic Edgar Allan Poe story "The Fall of the House of Usher". He once again expresses his interest in the occult by casting known members of the Church of Satan, Nikolas and Zeena Schreck. [www.flickeralley.com]